PENGARUH FAKTOR-FAKTOR KEPUTUSAN PEMBELIAN KONSUMEN DI TIKTOK SHOP (STUDI KASUS: DITUTUPNYA TIKTOK SHOP) - Ebenhaezer, Harvard; Fadjar, Nurman Setiawan (Journal of Development Economic and Social Studies, 2024)
This study aims to determine the relationship between income, discount, and influencer on purchasing decisions of 20 consumers at TikTok Shop who live in Malang and want to know the strength of the relationship. The issue raised is that TikTok Shop was dismissed by the government, where TikTok Shop is one of the important innovations and technological advances for Indonesia. The main theory used in this research is consumption theory. This research is a quantitative research with primary data using a Guttman scale, and tested with non-parametric statistical methods of Chi-Square and Kendall's Tau-B. The findings of this study are that income has a very strong correlation, discount has a very strong  correlation, and influencers have a strong correlation to purchasing decisions.  These results answer 3 problem formulations, which show that TikTok Shop is very important to consumers in Malang.  This result also shows that the ban of TikTok Shop is a loss for Indonesia because it can increase economic exchange and economic growth.